Sistem Pelayanan Jasa dan Penjualan Produk Percetakan Berbasis Web pada Proposter Indonesia - Elidjen Elidjen; Gandi Cahyadi; Mario Andika (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Various constraints related to the availability of up-to-date information services and product sales happen to ProPoster Indonesia, a business of digital printing and display services system run since 2002. ProPoster Indonesia needs to offer an easy access to services and online service sales of printing products to its customers and plans to expand its business services throughout Indonesia. These conditions initiate the development of web-based service and products sales system for ProPoster Indonesia. The main objectives are to overcome the difficulties in obtaining the latest information related to services and products and facilitate promotional printing services to all parts of Indonesia. The sequential linear process model is used to develop the overall system while literature study is done to enrich the insight to develop a better system. The user friendly system makes easy for customers to get the latest information that ultimately facilitate the service process and product sales.